Factors Influencing Behavioural Intention to Adopt the QR-Code Payment: Extending UTAUT2 Model - Suo, Wen Jing; Goi, Chai Lee; Goi, Mei Teh (2022)
This study aims to identify the factors which affect the consumers’ behavioural intention to adopt the Quick response code (QR-code) mobile payment. This study extends the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) with the personal innovativeness construct. This study reveals that performance expectancy, social influence, habit, price value, and personal innovativeness in information technology are significantly related to behavioural intention to adopt QR-code mobile payment. However, effort expectancy, facilitating conditions, and hedonic motivation are found to be statistically insignificant. This study presents one of the few empirical works investigating the role of consumer innovativeness and thus validates the inclusion of personal innovativeness as constructed in mobile payment adoption research. Findings from this study provide valuable insights for mobile payment application developers and mobile payment marketing teams. (Abstract by authors)